English-Speaking Habituation among EFL Students in Indonesian Pesantren: A Vygotskian ZPD Perspective - Lela Susanty; Ahmad Munawir; Hardimansyah Hardimansyah; Hafni Hafsah; Nurcaya (CV. Creative Tugu Pena, 2026)
This study investigates the process of English-speaking habituation among EFL students in a pesantren (Islamic boarding school) in East Java, Indonesia. Recognizing the growing importance of English in global communication, the research explores how pesantren-based programs support students in developing practical speaking skills within a religious and sociocultural context. Using an exploratory case study design and rely on Vygotsky’s zone of proximal development, data were collected through institutional documents, interviews with curriculum administrators, and participatory observation at the Foreign Language Development Institute (LPBA) of Pondok Pesantren Nurul Jadid. Findings reveal that structured initiatives such as Native Day and Level Mentoring play a crucial role in fostering immersion, peer-led learning, and confidence in using English. Students demonstrated adaptive strategies for negotiating meaning in English while managing interference from local languages like Madurese and Indonesian. The study highlights how consistency, learner autonomy, and institutional support contribute significantly to speaking proficiency. These insights offer practical implications for designing culturally responsive English curricula tailored to Islamic educational settings, reinforcing the need for pedagogical models that integrate language acquisition with students’ lived religious experiences.